Pengaruh Interaksi Edukatif dan Disiplin Belajar Terhadap Hasil Belajar Ekonomi Siswa Kelas X Di SMA Negeri 4 Sumbar - Kemala Nilam Syuri; Marwan Marwan (Jurnal Ecogen, 2019)
This study was conducted to find out (1) the effect of educative interaction and learning discipline to ward student economic learning outcomes, (2) the effect of educative interaction to ward student economic learning outcomes, (3) the effec of learning discipline to ward  economic learning outcomes. This research is descriptive and associative. The population in this study were specialy for sports school students of class X MIPA and IIS in West Sumatra 4 High School (Sports Giftedness) with 97 students. The total sample is determined by Slovin formula and propotional random sampling. From this formula, 80 students were obtained as research samples. Data collection techniques used in this study were questionnaires and documentation. The instrument of validity test uses Collected Item Total Colleration and for reliability testing using alpha coefficient formula. The prerequisite test is done by normality test, heterocedasticity test, and multicollinearity test. The technique used to analyze data is multiple linear regression analysis. Based on this study, it was found that (1) educative interaction and learning discipline had a positive and significant effect on the economic learning outcomes of class X students West Sumatra 4 High School (2) educational interaction had a positive and significant effect on the economic learning outcomes of class X students in West Sumatra 4 High School (3) learning discipline has a positive and significant effect on the economic learning outcomes of West Sumatra 4 High School. Keyword: educative interaction, student discipline, sport  school, learning outcomes